Prevention and management of human cytomegalovirus in pediatric HSCT recipients: A review - Hiskey, Lisa; Madigan, Theresa; Ristagno, Elizabeth H.; Razonable, Raymund R.; Ferdjallah, Asmaa (Frontiers in Pediatrics, 2022)
Cytomegalovirus (CMV), like other herpesviruses, has the unique ability to establish latent infection with subsequent reactivation during periods of stress and immunosuppression. Herpesviruses cause potentially devastating disease, particularly in hematopoietic stem cell transplant (HSCT) recipients. CMV is especially of concern in HSCT recipients given the high community seroprevalence, high risk of reactivation and high risk of transmission from HSCT donors to recipients causing primary infection after transplantation. The risk of CMV infection and severity of CMV disease varies depending on the underlying disease of the HSCT recipient, donor and recipient CMV status prior to HSCT, type of conditioning therapy in preparation for HSCT, allogeneic versus autologous HSCT, donor graft source, timing of infection in relation to HSCT, and other patient comorbidities. Different strategies exist for prevention (e.g., preemptive therapy vs. universal prophylaxis) as well as management of CMV disease (e.g., antiviral therapy, augmenting immune reconstitution, cytotoxic T-cell therapy). The purpose of this narrative review is to discuss diagnosis, prevention, and management of CMV infection and disease at different stages of HSCT, including key points illustrated through presentations of complex cases and difficult clinical scenarios. Traditional and novel strategies for CMV management will be discussed in the context of these unique clinical cases.